Determinants of surgically induced menopause in rural North Karnataka - Sudhirgouda Honagouda Patil; Naresh Kumar Tyagi; Jang Bahadur Prasad (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of the study was to quantify the effect of surgically induced menopause (SIM) on quality of life as assessed by religion, body mass index (BMI), sexual problem, menstrual history, blood spotting after intercourse, menopausal symptoms, and psychological disorder in the age group of 40-55 years of women. Materials and Methods: In this cross-sectional study, 712 rural women, comprising of 40 women (aged 40-55 years) with SIM, were surveyed, by inverse cluster sampling with proportional to population size. The aim was to study SIM and its determinants; menopause anthropometric data, menopause symptoms, and associated psychosocial symptoms. The data was analyzed using bivariate and multivariate techniques. Results: Around 6.4% of Hindu women had SIM, followed by Muslim (6.2%) and others (1.1%). SIM was significantly high in BMI group <25. The differences of SIM in regularity of menstruation were significant. Similar results were observed in sexual problem, menstrual flow, blood spotting after intercourse, blood spotting between periods, pain in periods, physical and mental exhaustion, heart discomfort, sleep problem, irritability, and dryness of the vagina. The sexual activity significantly hampered after SIM, further, unadjusted Odds Ratios (ORs) were not in line with adjusted OR. With regularity of menstruation problem, the SIM increases significantly, as indicated by adjusted and unadjusted ORs, the similar results were seen by menstrual flow and blood spotting after intercourse. The SIM by adjusted and unadjusted ORs was similar in other determinants. The Logistic regression model has been calibrated for sensitivity and specificity above 90% and accuracy as high as 97.8%. The modulated probabilities have been provided for the users of the model. Conclusion: The results of the bivariate analysis of surgical menopause by its covariates and regression model constructed are valuable for health-care providers, as reference for diagnosis, and to pacify patients for consequences of the prognosis.